Commodity Prices Shocks and the Balance Sheet Effect in Latin America (2018)
Emerging market economies(EMEs), particularly the commodity exporterones,are ex- posed to world’s dynamics through different channels. In this paper,we consider the role of (exogenous) commodity prices shocks in explaining business cycles in EMEs,by proposing a financial transmission mechanism: the balance sheet effect. Our hypothesis is that a nega- tive commodity price shock increases the firm’s external debt and the cost of the new debt. In consequence,the aggregate investment decreases amplifying the output contraction.To test it,we estimate a series of VAR models using quarterly data on corporate external debt, nominal exchange rate, EMBI+ spreads, the local currency value of external debt to nomi- nal GDP ratio and real GDP,covering the period 2000-2017. We do this for Latin America and then, we focus on five particular economies: Brazil, Chile, Colombia, Mexico and Peru. We find that balance sheets do matter and they exacerbate the output’s contraction when the commodity price shock is negative. We also find that, turning the financial channel off, the real GDP cumulative response in Latin America is smaller than in the unrestricted model. Finally, we find no evidence on the existence of the balance sheet effect for Chile.